Knowledge, attitude and practice towards blood donation and its associated factors among university students in Shah Alam, Malaysia - Elnajeh, Maged; Ghazi, Hasanain Faisal; Abdalqader, Mohammed A.; Baobaid, Mohammed Faez (International Journal Of Community Medicine And Public Health, 2017)
Background: The aim of this research is to find out the relationship between knowledge, attitude, practice towards blood donation and its association with socio-demographic factors, field of study, and blood groups of the students. Methods: A cross-section study was conducted among 679 university students using self-administered questionnaire. The questionnaires consist of 4 parts mainly socio-demographic data, knowledge towards blood donation (10 questions), attitude towards blood donation (6 questions) and practice towards blood donation (1 question). Results: Majority of respondents have good knowledge (97.1%), good attitude (88.8%); however majority of them have poor practice (70.3%). There was an association between Knowledge, and gender (p=0.001), attitude and field of study, blood group (p<0.001, 0.001 respectively). By using regression analysis, the only factor associated with Knowledge was gender with adjusted OR of 5.2. Conclusions: Most of the students have good knowledge and attitude but they have poor practice towards blood donation. More promotion and education are needed to encourage students for more blood donation in the future.